PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP HASIL BELAJAR BIOLOGI SISWA PADA MATERI SISTEM PERTAHANAN TUBUH KELAS XI SMA - Ade Sitio, Dian Mars; Situmorang, Masni Veronika; Siagian, Gunaria (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
The purpose of this study is to determine: The effect of Course Review Horay Learning model on the learning outcomes of biology students in class XI material of the body's defense system at Senior hight school 1 Sidamanik in the academic year 2021/2022. This type of research is a quantitative research in which the research population includes all students of class XI SMA Negeri 1 Sidamanik in the academic year 2021/2022, so up to 175 students. The samples of this study were 70 students of classes XI IPA 2 and XI IPA 3. The instrument used in this study was a multiple choice test with a quasi-experimental research type and a non-equivalent control group design. The independent variable is Horay Course Overview and the dependent variable is learning outcomes. The results of the students' data were compared with the norms, and the study result data were analyzed using the N-Gain test and Independent Sample T-Test. The results showed that the "Course review" method had a great impact on the results of the education of the students of the 11th grade of the 6th grade of Sidamanik in the subject of biology, the material of the body's defense system. The learning outcomes of the students in the experimental class achieved good characteristics, and the control class achieved only sufficient characteristics. The experimental group mean test was 83.14 and the control class mean post test was 76.57. It shows that the N-profit index of the experimental group is 0.706 (high), while the N-profit index of the control class is 0.452 (average). The results of the independent sample test showed the value of tcount(4.226) > ttable(1.995), which means that the Course Review Method can improve the results of students' learning about the immune system and the impact value. Sig. (2-tailed) < 0.05 is 0.000. The conclusion is that Horai's course review study method affects students' learning outcomes in biology. Kata kunci: Course Review Horay, Hasil Belajar